2012
DOI: 10.1074/jbc.m112.399667
|View full text |Cite
|
Sign up to set email alerts
|

Serratia marcescens Induces Apoptotic Cell Death in Host Immune Cells via a Lipopolysaccharide- and Flagella-dependent Mechanism

Abstract: Background:The pathogenic mechanism of Serratia marcescens is poorly understood. Results: S. marcescens kills immune cells via an lipopolysaccharide-and flagella-dependent mechanism. Conclusion: S. marcescens suppresses innate immunity by killing immune cells.Significance: This is the first evidence to suggest that S. marcescens evades the immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 57 publications
1
33
0
Order By: Relevance
“…1B). We and others have demonstrated that fewer than 10 colony-forming units of S. marcescens kills insects, including silkworms (15,25). We therefore hypothesized that the above phenomenon, suppression of the injurydependent reduction in hemocyte numbers by S. marcescens, is responsible for the high virulence of S. marcescens against silkworms.…”
Section: Decrease In Silkworm Hemocyte Number By Injury Stimulation Amentioning
confidence: 94%
See 4 more Smart Citations
“…1B). We and others have demonstrated that fewer than 10 colony-forming units of S. marcescens kills insects, including silkworms (15,25). We therefore hypothesized that the above phenomenon, suppression of the injurydependent reduction in hemocyte numbers by S. marcescens, is responsible for the high virulence of S. marcescens against silkworms.…”
Section: Decrease In Silkworm Hemocyte Number By Injury Stimulation Amentioning
confidence: 94%
“…In the course of our studies of S. marcescens pathogenesis using the silkworm infection model (15), we found that the number of freely circulating hemocytes in silkworms increased immediately after infection. We speculated that the bacteria inhibited the adhesion of hemocytes to the body cavity and tissues.…”
mentioning
confidence: 91%
See 3 more Smart Citations